Risk Factors for Nutritional Rickets in Children under 36 months: A Civil Hospital Case Study - Sangeeta Santosh; Fehmina Arif; Hina Raess (ziauddin University, 2024)
Background: Nutritional rickets is a common problem in Pakistan especially in Karachi with majority of the population living in enclosed housing and slums having limited or no sun exposure. There is a dearth of significant data regarding rickets in Pakistan especially in Sindh which emphasizes the need for further research. This study can be a foundation for other studies regarding strategies for prevention and early diagnosis of rickets. Objectives: To determine the clinical presentation and identify risk factors for nutritional rickets in children less than three years of age. Methods: A cross sectional study conducted in the department of pediatrics DUHS/CHK from June 11, 2007 to December 10, 2007. Fifty patients aged two months to thirty six months presenting with the clinical manifestation of rickets were included in the study. Information recorded included symptoms, socioeconomic status, feeding patterns, sun exposure, clothing, housing and malnutrition. Diagnosis was based on clinical signs, serum levels of alkaline phosphatase, calcium, phosphorus and radiological changes in X-ray wrist joint. Results: Approximately 60% reported a weight for height less than ISD criteria set by WHO. Of the total assessed 58% percent were exclusively breast fed, 30% partial breast fed and 12% on formula milk. Weaning age was not reached in 20% of the children. Complementary feeding initiated late for 40% of the children with 78% percent exposed to sunlight less than 30 minutes per day and. Gross motor delay existed in 30% of children and hypocalcaemia convulsions in 14%. Past H/O repeated was in 32% had 22% had persistent/recurrent diarrhea. Conclusion: Exclusivity breast feeding to complementary feed, inadequate exposure to sunlight and delayed introduction of complementary foods are the main risk factors for the development of nutritional rickets which can manifest itself in the form of ARI and diarrhea. KEY WORDS: Rickets, Vit-D Deficiency, Biochemical Abnormalities.